Reproductive Hormones Modulate Oxidative Stress in Alzheimer’s Disease - Barron, A.; Fuller, S.; Verdile, Giuseppe; Martins, R. (Mary Ann Liebert, Inc. Publishers, 2006)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by gradual cognitive decline, impairments in speech and language, and dysfunction in the sensorimotor systems, culminating in complete reliance on nursing care. Oxidative stress, caused by an imbalance in the pro-oxidant/antioxidant mechanisms in the body, has been implicated in AD pathogenesis, as in many other age-associated diseases such as atherosclerosis, Parkinson disease, and amyotrophic lateral sclerosis. Although the hormones estrogen, progesterone, testosterone, and luteinizing hormone are best known for their roles in reproduction, many studies show these hormones have other roles, including neuroprotection. Changes in the levels of these hormones that occur in reproductive senescence are hypothesized to increase risk of AD, as a result of reduced protection against oxidative insults. The Aß peptide, overproduction of which is thought to be a key pathogenic event in the development of AD, is neurotoxic, most likely due to its ability to promote oxidative stress. The reproductive hormones are known to influence Aß metabolism, and this review discusses the beneficial and detrimental effects these hormones have on Aß production and oxidative stress, and their relevance in potential AD therapies.